The role of group communication in the meaning-making processes about agency-hired workers' employment status - Romanes, Rojean C.; Piala, Julius Neil A. (2019)
This study generally explored how the interactions and communication of the members of the following groups: the hiring agency and the deployed workers, influence the way they construct their realities about contractualization and the workers? employment status. The respondents of this thesis were TopServe, the hiring agency, and the workers that they hired for Jollibee. The researcher used a qualitative method in gathering and analyzing data. Hence, series of key informant interviews and focused-group discussions with the groups involved in the trilateral employee arrangement were done to gather relevant information for the study. Results have shown that various communication channels and interventions were utilized by the different groups to communicate and talk about the agency-hired workers? employment status. Hence, these communication channels and interventions has played a vital role in the meaning making process of the groups. Furthermore, even if there are face-to-face interactions that were the management orients and instill in the minds of the workers the following ideas: 1) that they work for TopServe, and not for Jollibee, and 2) that they are not contractual workers, the agency-hired workers still think otherwise. These ideas that are instilled by the management in the minds of those workers were debunked because of the own meaning-making processes made by the workers within themselves.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019